2014
DOI: 10.1128/jvi.02086-13
|View full text |Cite
|
Sign up to set email alerts
|

Novel Woodchuck Hepatitis Virus (WHV) Transgene Mouse Models Show Sex-Dependent WHV Replicative Activity and Development of Spontaneous Immune Responses to WHV Proteins

Abstract: HBV has a very narrow host range and can infect only humans and higher primates such as chimpanzees (3, 4). However, experiments using chimpanzees are costly and require both scientific and ethical justification. HBV transgenic (Tg) mice have allowed examination of the influence of viral and host factors on HBV pathogenesis and replication and assessment of the antiviral potential of pharmacological agents (5). For example, the transfer of HBsAg-specific CD8 ϩ T cells into these mice led to the inhibition of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…We recently showed that therapeutic vaccination elicits potent CD8 + T‐cell responses and reduces WHV replication in 1217 Wtg mice . We also observed gender‐related differences in WHV replication in these Tg mice . Therefore, we chose this mouse model to study the impact of gender on the efficacy of a therapeutic vaccination against hepadnaviral infection.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently showed that therapeutic vaccination elicits potent CD8 + T‐cell responses and reduces WHV replication in 1217 Wtg mice . We also observed gender‐related differences in WHV replication in these Tg mice . Therefore, we chose this mouse model to study the impact of gender on the efficacy of a therapeutic vaccination against hepadnaviral infection.…”
Section: Resultsmentioning
confidence: 99%
“…In this strain WHV particles are not shed into the bloodstream. Male WtgS – mice show stronger WHV replication in the liver than females and elevated ALT levels (http://onlinelibrary.wiley.com/doi/10.1002/hep.29155/suppinfo). Male and female WtgS – mice were immunized with the heterologous DNA prime‐AdV boost regimen as described above (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations